SAT0256 THE ROLE OF FAST-TRACK ULTRASOUND IN PREVENTING EARLY COMPLICATIONS AND RELAPSES IN GIANT CELL ARTERITIS. (2nd June 2020) - Delvino, P.; Monti, S.; Bartoletti, A.; Bellis, E.; Brandolino, F.; Milanesi, A.; Montecucco, C.
Abstract : Background: Giant Cell Arteritis (GCA) is the most common form of primary systemic vasculitis, mainly affecting adults over 50 years old. Permanent visual loss (PVL) is one of the most feared complications, occurring in about 20% of cases, typically prior to initiation of high-dose glucocorticoid (GC) therapy. Color-duplex sonography (CDS) of temporal arteries (TAs) and large vessels (LVs) is recognized as a first-line diagnostic tool for patients with suspected GCA. A fast track approach (FTA), incorporating CDS has been associated to a significant reduction of PVL in two retrospective studies 1, 2 . Objectives: To assess the impact of FTA on PVL and risk of relapses during follow-up compared to conventional care prior to the introduction of the FTA in our rheumatology clinic. Methods: Patients with new-onset GCA evaluated in our department from January 1998 to September 2019 were included in the study. The FTA approach for GCA was implemented since October 2016. The diagnosis of GCA was based on positive TAs and/or LVs CDS and/or a positive TA biopsy and clinical signs and symptoms of GCA. All patients were clinically examined by the same rheumatologist who performed the CDS. PVL was defined as total visual impairment in one or both eyes. Data on baseline clinical features and later outcomes were collected. Results: 153 patients were included: 115 females (75.2%), mean age at diagnosis 71.6±8.2 years. Of these, 112 patients (73%) were evaluated conventionally and 41 (27%) with FTA. Patients in the FTA group were older (P=0.0002), presented more frequently with polymyalgia rheumatica symptoms, weight loss, jaw or tongue claudication and scalp tenderness (P<0.05 for all comparisons). The median duration of follow-up in the FTA group was shorter compared with the conventional group (1.5 vs 5.8 years). PVL occurred in 22 (19.6%) patients in the conventional group compared to 5 patient (12.2%) in the FTA, leading to a reduction of 37.9% in the relative risk of PVL with the FTA approach. Cumulative incidence of relapses and time to first relapse did not change after FTA introduction (P>0.05) (Fig. 1). Conclusion: The application of a FTA in GCA resulted in a significant reduction of PVL. However, the relapse rate did not seem to be influenced by the FTA, highlighting the need to implement further management strategies, besides earlier diagnosis and prompt initiation of GC, that would impact the course of the disease during long-term follow-up References: [1]Patil P, Williams M, Maw WW et al. Fast track pathway reduces sight loss in giant cell arteritis: results of a longitudinal observational cohort study. Clin Exp Rheumatol 2015;33(Suppl 89):S-103-6. [2]Diamantopoulos AP, Haugeberg G, Lindland A, Myklebust G. The fast-track ultrasound clinic for early diagnosis of giant cell arteritis significantly reduces permanent visual impairment: towards a more effective strategy to improve clinical outcome in giant cell arteritis? Rheumatology 2016;55:66_70. Disclosure of Interests: None declared